India : Environmental Sustainability in the 1990s, A Country Assistance Evaluation - Ringskog, Klas; Chow, Nola (World Bank, Washington, DC, 2014)
India's environmental problems are deep-rooted and severe. Estimates of annual environmental damage range from 4.5 percent to 8 percent of gross domestic product (GDP), in line with annual economic growth. Since 1990 the World Bank has lent India 1.94 billion dollars for 19 projects to mitigate environmental damage and another 97 million dollars was granted under global environmental facility (GEF) and Montreal protocol trust funds for four projects to protect the global environment. The Bank has also supported a spectrum of economic and sector work (ESW) that address environmental issues based on country assistance strategies. The report identifies eight conclusions for the Bank s future environmental assistance to India: integrate safeguards earlier in the project cycle; provide alternatives to public sector management of water supply and sewerage systems; greatly expand support of sanitation programs; air pollution needs to be targeted as a priority measure; step up efforts to promote rational pricing of natural resources; monitoring and enforcement of environmental standards is lagging and undermines the whole regulatory effort; links between poverty reduction and ecological balance must be more fully documented; and better recognition of global environmental threats will also address local concerns.